Examining Predictive Validity of the Level of Service Inventory–Ontario Revision (LSI-OR) Substance Abuse Subscale for Different Types of Substance Users - Davis, Paula (Criminal justice and behavior, 2020)
Substance abuse is a risk factor for recidivism that is commonly assessed by the Level of Service Inventory-Ontario Revision (LSI-OR) via the Substance Abuse subscale. Research has yet to examine the predictive validity of this subscale relative to types of substances abused. To explore this, substance abuse history, LSI-OR information, and recidivism were coded for a sample of 498 individuals convicted of a crime with a current substance abuse problem. These individuals were classified by the types and number of substances abused. Results of this study provide some evidence supporting the predictive validity of the LSI-OR Substance Abuse subscale. Furthermore, we found preliminary evidence supporting the predictive validity of the subscale for substance abusers relative to types of substances abused and for those who abuse a single substance versus multiple substances. These results have implications for research, policy, and correctional practice.